Reflections about the social determinants of art and design: noise music in Latin America and Asia - Dimitri della Faille (Kepes, 2015)
The paper is based on the author’s experience performing noise or experimental music in Latin America, East and South East Asia. In this paper, the author reflects on some social determinants of art and design. Dimensions such as technology, territory, identity, social characteristics and social acceptance are discussed. Additional topics such as class, gender, politics are covered. The author concludes that these do not shape the practice of noise music, they are also elements which provide frameworks on which artists and designer built